As narrativas orais crioulo-guineenses - Couto, Hildo Honório do (2011)
ABSTRACT: The main purpose of this essay is to show that the storias, i.e., Kriol fables are a good testing case for the study of the interrelationships between language and world. They arouse out of the struggle of their users with the world in their everyday life. For this reason, they reflect the environment in which Guineans live and work. This reflex is seen not only in the narratives' plot but also in the specific vocabulary they contain.